2004
DOI: 10.1111/j.0300-9475.2004.01373.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylated CpG‐Containing Plasmid Activates the Immune System

Abstract: Bacterial DNA differs from mammalian DNA by the presence of unmethylated cytosine-phosphate-guanosine (CpG) motifs. The immunostimulatory properties of a DNA vaccine have been suspected to be associated with these motifs. The aim of this study was to assess the inactivation of the immunostimulatory potential of a plasmid after methylation of its CpG motifs. We constructed two identical non-coding plasmids, and one of these was de novo methylated on its CG sequences. A single administration of recombinant antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
2
11
3
Order By: Relevance
“…Our results are in contrast to those of previous studies in which the CpG motifs were shown to only increase cell-mediated immune responses [17][18][19] or antibody responses [7,16]. In some cases, the CpG motifs may even have no effect or an inhibitory effect on immunogenicity of DNA vaccines [8,9,29,30].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are in contrast to those of previous studies in which the CpG motifs were shown to only increase cell-mediated immune responses [17][18][19] or antibody responses [7,16]. In some cases, the CpG motifs may even have no effect or an inhibitory effect on immunogenicity of DNA vaccines [8,9,29,30].…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in contrast to those of previous studies in which the CpG motifs were shown to only increase cell-mediated immune responses [17][18][19] or antibody responses [7,16]. In some cases, the CpG motifs may even have no effect or an inhibitory effect on immunogenicity of DNA vaccines [8,9,29,30].Additionally, equivalent total or isotypes antibody responses, lymphocyte proliferative responses, cytokine profiles, and protective responses were observed between all groups receiving corresponding plasmid DNA vaccines containing ampicillin-and kanamycin-resistant genes. These results show that the immunogenicity of DNA vaccines is not affected by the antibiotic selection gene in the plasmid backbone, indicating that the enhanced immunogenicity of plasmids vaccines is attributed only to modification with CpG motifs.…”
contrasting
confidence: 99%
“…Perhaps more importantly, it is acknowledged here that the therapeutic potential of oblimersen is enhanced due to the fact that it likely mediates anticancer activity through several mechanisms. As shown here and by others (34,(41)(42)(43), oblimersen effectively inhibits expression of Bcl-2. It is accepted that the oligonucleotide sequence used can stimulate the immune system in a manner that can indirectly result in antitumor effects.…”
Section: Discussionsupporting
confidence: 87%
“…Bacterial DNA was shown to activate neutrophils via signaling that occurred regardless of unmethylated CpG and did not involve TLR9 (39). Langerhans' cell emigration and cytokine production were also stimulated by methylated CpG-containing plasmid DNA (11). DNA-mediated macrophage activation was dependent on the presence of unmethylated CpG motifs, but CpGmethylated DNA was also capable of activating macrophages at high concentrations (31).…”
Section: Discussionmentioning
confidence: 99%